Fault Tolerant Control of Power Grids. (20th February 2014) - Odgaard, P.F.; Aubrun, C.; Majanne, Y.; Odgaard, P. F.; Aubrun, C.; Majanne, Y.
SUMMARY This special issue contains article on fault detection and isolation and fault tolerant control methods applied to different aspects of modern power grids, both for detection, isolation and accommodating faults in the power grid, and for detection, isolation and accommodation of faults in power generating units. Copyright © 2014 John Wiley & Sons, Ltd.